Long term neurological dysfunction and neonatal hypoglycaemia after diabetic pregnancy. Issue 3 (1st November 1998) - Stenninger, E; Flink, R; Eriksson, B; Sahlèn, C
Abstract : AIM: To determine if children born to mothers with diabetes mellitus during pregnancy, who subsequently developed neonatal hypoglycaemia, experienced long term neurological dysfunction. METHODS: Thirteen children with, and 15 without, neonatal hypoglycaemia (blood glucose < 1.5 mmol/l) were randomly selected from a larger cohort and investigated at the age of 8 years. They were also compared with 28 age matched healthy controls. RESULTS: Children with neonatal hypoglycaemia had significantly more difficulties in a validated screening test for minimal brain dysfunction than controls and were also more often reported to be hyperactive, impulsive, and easily distracted. On psychological assessment, they had a lower total development score than normoglycaemic children born to diabetic mothers, and control children. CONCLUSIONS: Neonatal hypoglycaemia in diabetic pregnancy was associated with long term neurological dysfunction related to minimal brain dysfunction/deficits in attention, motor control, and perception.